Field co-inoculation of Bradyrhizobium sp. and Pseudomonas increases nutrients uptake of Vigna radiata L. from fertilized soil. (21st April 2023) - Shah, Ghulam Abbas; Sadiq, Maqsood; Iqbal, Zahid; Shakoor, Noman; Shahid, Muhammad; Aulakh, Azhar Mehmood; Arthur, Kamusiime; Khan, Nadeem; Ismail, Iqbal M.I; Rashid, Muhammad Imtiaz
Abstract: Nitrogen (N) and phosphorus (P) deficiency in soils limit plant growth. Consequently, chemical fertilizers are applied to fulfill crop nutrient demands. However, low nutrient utilization can make these fertilizers unprofitable for low-income smallholding farmers. Therefore, we studied the influence of Bradyrhizobium sp. and phosphate-solubilizing bacteria ( Pseudomonas ) on N and P utilization by mungbean crop from fertilized nutrient-deficient soil. We inoculated novel Bradyrhizobium sp. TAL-377 and Pseudomonas sp. 54RB strains alone or their combination with seeds of mungbean varieties (C-MUNG, NM-06, and NM-11). A basal dose of chemical fertilizers was applied at the rate of 60 kg N and 90 kg P ha −1 in the form of urea and single super phosphate in all plots before crop sowing. All inocula increased soil mineral N and P compared to control ( P < 0.05). Co-inoculation increased mineral N by 30%, 18%, and 18% than Bradyrhizobium sp. alone and increase in P was 22, 29 and 43% than Pseudomonas sp. in C-MUNG, NM-06, and NM-11, respectively. This resulted in 35%, 45%, and 36% higher shoot N uptakes than Bradyrhizobium sp., and 46%, 84%, and 62% higher shoot P uptake than Pseudomonas sp. in the varieties. Similarly, root nodulation, mungbean grains, and biological yields were higher in co-inoculation treatments than single strain ( p < .05). Hence, co-inoculation of Bradyrhizobium sp. and phosphorus solubilizing bacteria ( Pseudomonas sp.) is a vital strategy to increase mungbean growth, yield, N and P utilization from chemical fertilizers applied in nutrient-deficient soils.